Evaluation of 2013 Curriculum Implementation in The Achievement of Gradical Competency Standars in Mathematic About Mathematics Literation in SMAN 1 Menganti Gresik - Fitriyanto, Gilang Ilham (International Journal for Educational and Vocational Studies, 2020)
This study aims to determine the impact of the implementation of the 2013 curriculum on education units and the achievement of graduate competency standards for each student in the education unit and identify the impact and constraints of the implementation of the 2013 curriculum in mathematics and mathematics literacy related to translating story sentences in mathematical symbols and sentences, write down, and translate questions.This evaluation study uses a countenance stake model with a quantitative approach. The method used is documentation, observation and questionnaire or questionnaire. Evaluation research subjects are 3 mathematics teachers and 34-35 samples of class XI students with curriculum object research documents, teacher documents, mathematics literacy skills and mathematics learning implementation in 2013 curriculum. The results showed the principle of curriculum development and curriculum components of SMAN 1 Menganti getting an average score of 100, component compilation of teacher documents amounting to 78, 25, implementation of 2013 curriculum learning mathematics subjects getting an average score of 79, 2013 curriculum authentic evaluation of the teacher's eyes lessons of 68.57, mathematical literacy skills obtained an average score of 70. Based on the results of the 2013 curriculum evaluation research at SMAN 1 Menganti, it can be concluded that the development and components of the 2013 curriculum have met the standards and refer to the graduate competency standards (SKL) but still need to improve teacher competencies, especially mathematics teachers and improve students' mathematical literacy abilities.